Hubungan Kunjungan Industri dengan Peningkatan Pemahaman Sistem Produksi dan Kemampuan Berpikir Kritis Mahasiswa Fakultas Teknologi Industri UNUGHA Cilacap (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
Industrial visits are widely recognized as an experiential learning approach that bridges the gap between theoretical knowledge and real industrial practices in engineering education. This study aims to examine the relationship between industrial visits and the improvement of production system understanding and critical thinking skills among students of the Faculty of Industrial Technology at Universitas Nahdlatul Ulama Al-Ghazali (UNUGHA) Cilacap. A quantitative approach with a one-group pretest–posttest design was employed. The participants consisted of 43 industrial engineering students who took part in industrial visits to PT Dirgantara Indonesia and the National Research and Innovation Agency (BRIN) in Bandung. Data were collected using Likert-scale questionnaires and analyzed through Paired Sample t-Test. The results reveal a significant increase in students’ understanding of production systems, with mean scores rising from 64.23 (pretest) to 81.47 (posttest) (p < 0.05). Similarly, critical thinking skills showed a significant improvement, increasing from a mean score of 63.05 to 83.12 (p < 0.05). These findings demonstrate that industrial visits have a substantial positive impact on enhancing students’ academic competencies. This study highlights the importance of systematically integrating industrial visits into the industrial engineering curriculum to strengthen learning outcomes and improve graduates’ readiness for industrial challenges.